Warm and touching tears: tearful individuals are perceived as warmer because we assume they feel moved and touched - Zickfeld, J. H. (2019)
Recent work investigated the inter-individual functions of emotional tears in depth. In one study (Van de Ven, N., Meijs, M. H. J., & Vingerhoets, A. (2017). What emotional tears convey: Tearful individuals are seen as warmer, but also as less competent. British Journal of Social Psychology, 56(1), 146–160. Https://doi.org/10.1111/bjso.12162) tearful individuals were rated as warmer, and participants expressed more intentions to approach and help such individuals. Simultaneously, tearful individuals were rated as less competent, and participants expressed less intention to work with the depicted targets. While tearful individuals were perceived as sadder, perceived sadness mediated only the effect on competence, but not on warmth. We argue that tearful individuals might be perceived as warm because they are perceived as feeling moved and touched. We ran a pre-registered extended replication of Van de Ven et al. Results replicate the warmth and helping findings, but not the competence and work effects. The increase in warmth ratings was completely mediated by perceiving feeling moved and touched. Possible functions of feeling moved and touched with regard to emotional tears are discussed.